Basement membrane patterning by spatial deployment of a secretion-regulating protease - Hui-Yu Ku; David Bilder (Proceedings of the National Academy of Sciences, 2025)
While paradigms for patterning of cell fates in development are well established, paradigms for patterning morphogenesis, particularly when organ shape is influenced by the extracellular matrix (ECM), are not. Morphogenesis of the Drosophila egg chamber (follicle) depends on anterior–posterior distribution of basement membrane (BM) components such as Collagen IV (Col4), whose gradient creates tissue mechanical properties that specify the degree of elongation. Here, we show that the gradient is not regulated by Col4 transcription but instead relies on posttranscriptional mechanisms. The metalloprotease ADAMTS-A, expressed in a gradient inverse to that of Col4, limits Col4 deposition in the follicle center and manipulation of its levels can cause either organ hyper- or hypoelongation. We present evidence that ADAMTS-A acts within the secretory pathway, rather than extracellularly, to limit Col4 incorporation into the BM. High levels of ADAMTS-A in follicle termini are normally dispensable but suppress Col4 incorporation when transcription is elevated. Meanwhile, the terminally expressed metalloprotease Stall increases Col4 turnover in the posterior. Our data show how an organ can employ patterned expression of ECM proteases with intracellular as well as extracellular activity to specify BM properties that control shape.